Performance Evaluation of a 7000 Liter FiberGlass Biodigester for Biogas Production - Khalil, Fakhrul Irfan; Amuddin; Widhiantari, Ida Ayu; Ridho, Rosyid; Zulfikar, Wahyudi (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2026)
This study aims to evaluate the operational performance of a 7000-liter fiberglass biodigester that was revitalized and modified at the Power and Agricultural Machinery Laboratory, Faculty of Food Technology and Agroindustry, University of Mataram. The fiberglass biodigester was developed as an alternative to conventional concrete biodigesters, which are prone to structural damage and exhibit limited operational efficiency, particularly in earthquake-prone regions. The research was conducted as an observational case study through performance monitoring of the biodigester during 40 days of continuous operation following system repair and modification. Cow manure was used as the substrate, mixed with water at a 1:2 ratio (by volume). The monitored parameters included fermentation temperature, substrate pH, gas pressure, daily biogas volume, gas composition, and combustion quality. The results showed that the biodigester operated stably at temperatures ranging from 27 to 31 °C and near-neutral pH conditions, with a maximum daily biogas production of 4.43 m³/day and an average of 1.73 m³/day throughout the monitoring period. The methane content ranged from 52 to 61%, while hydrogen sulfide concentration was reduced to approximately 150 ppm after gas purification, indicating that the biogas was suitable for combustion with a heating value of up to 21 MJ/m³. These findings demonstrate that the fiberglass biodigester exhibits good operational performance and has strong potential for application as a renewable energy system at campus and community scales, supporting sustainable livestock waste management.